Entangling a single NV centre with a superconducting qubit via parametric couplings between photons and phonons in a hybrid system. Issue 21 (29th November 2016) - Li, Zhen-Fang; Li, Peng-Bo; Li, Fu-Li
Abstract : We propose an efficient scheme for generating entangled states between a single nitrogen-vacancy (NV) centre in diamond and a superconducting qubit in a hybrid set-up. In this device, the NV centre and the superconducting qubit couple to a nanomechanical resonator and a superconducting coplanar waveguide cavity, respectively, while the microwave cavity and the mechanical resonator are parametrically coupled with a tunable coupling strength. We show that, highly entangled states between the NV centre and the superconducting qubit can be achieved, by means of the Jaynes–Cummings interactions in the NV-resonator and qubit-cavity subsystems which transfer the entanglement between the vibration phonons and the cavity photons to the NV centre and the superconducting qubit. This work may provide interesting applications in quantum computation and communication with single NV spins and superconducting qubits.